Chiari Malformation Type 1 as Cause of Recurrent Pneumonia with Failure to Thrive - Roy, Soumya; Chakrabartty, Subroto (Journal of Nepal Paediatric Society, 2017)
Diagnosing the cause of recurrent pneumonia with failure to thrive (FTT) can be difficult. A nine months age presented with recurrent pneumonia and failure to thrive. Investigation for the same led to the diagnosis of Chiari 1 malformation. Screening for latent neurological disorders should be done in such patients. J Nepal Paediatr Soc 2016;36(3):288-290